A Component Loan Application Design and Check Loan Transactions for Dependent Free Letters at the AI Building at The State Polytechnic of Malang Web-Based - Cindy Dwi Puspita Sari; M. Nanak Zakaria; Rieke Adriati Wijayanti (Politeknik Negeri Malang, 2022)
The development of information and communication technology is a major need in this advanced era with the aim of all computerized activities ranging from office work, banking, administration, libraries, education, government, organizations, and many more that are very dependent on the sophistication of computers and existing applications. inside it. In the AI ??Polinema Building in the component borrowing room, the component borrowing system and transaction checking for existing collateral-free letters still use the conventional system which causes ineffectiveness in component borrowing and free-of-liberty letter processing. Therefore, a research will be conducted to design a component loan application and check loan transactions for a Web-based free letter. Based on the problems above, in this study the researchers created a system that can support component lending and checking loan transactions for Web-based free letters. This system uses the Visual Studio Code application. From this study, it was found that the system that has been created by the researcher can run well and can help improve the performance of the technicians on duty in the loan room as well as the effectiveness of time for students in the loan process and managing free letters.